A solanesyl-diphosphate synthase localizes in glycosomes of Trypanosoma cruzi - Ferella, Marcela (2006)
Fil: Ferella, Marcela. ANLIS Dr. C. G. Malbrán. Instituto Nacional de Parasitología "Dr. M. Fatala Chabén" (INP); Argentina.